The Effectiveness of Using Scrabble Game to Teach Vocabulary - Qatrunnada, Febrilia Hasna; Zuhriyah, Mukminatus (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2024)
Vocabulary is crucial for effective communication, especially in the global context where English is an essential international language. However, English proficiency at one of the state junior high schools in Perak Jombang, East Java, remains low. This research aims to determine the effectiveness of the Scrabble game in improving vocabulary mastery in class VII-I in one of the state junior high schools at Perak Jombang, East Java. This research used a pre-experimental design with a sample of twenty-five students. Data collection included pre-test and post-test assessments, analyzed using the Sample Paired t-test formula with a significance level of 0.05 (Î±=5%). The results revealed a two-tailed significance value (sig.) of 0.000, which is less than 0.05. ttable calculation at significance alpha= 5% is 2.063 while the tcount 4.203 (tcount > ttable). This indicates that the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted. These findings demonstrate that the Scrabble game effectively enhances students' vocabulary mastery. It is hoped that this research can serve as a reference for other researchers to explore using Scrabble to improve vocabulary among junior high school students.